COMPARISION OF IgG, IgM-IFA AND IgG, IgM-ELISA IN TOXOPLASMA GONDII SEROLOGY - TALARI, S.A.; ARBABI, M.; VAKILI, Z.; AHMADI, H. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
To consider the incidence of toxoplasmosis and in order to comparison its IFA and ELISA IgG and IgM, this study from March 2002 to 2003 in Kashan was undertaken. In this cross sectional study, 600 people (300 men, 300women) referring to Central laboratory of University for toxoplasmosis testing, who were negative for ANA and RF were selected. The patient's data including age, sex, occupation, residency and educational level were recorded. 5 cc venous blood were taken and serums were frizzed. Tests were done by two methods. In IFA method, the IgG-IFA and IgM-IFA kits produced by Baharafshan and in ELISA method, the Trinity-Biotech kits were used. In the first method persons with titer 1/200 or more (witness group) and in second one, those with ISR (Immune Stamts Ratio) more than 1.1 (case group) were considered positive, Then, sensitivity and specificity of ELISA in comparison with IFA were calculated. The research showed that 89% patients were positive with both IgG-ELISA and IgG-LFA methods 11% were positive only with IgG-IFA. IgG- ELISA sensitivity in comparison with IgG-IFA was 89%, its specificity 100%, positive indicative value 100% and negative indicative value 97.8%. Test output was 98.2%. Also 11% patients had anti toxoplasma IgM by two methods and 3% were positive only with IFA method. Sensitivity of IgMELISA in comparison with IgM-IFA was 78.6%, specificity 99.6%, positive indicative value 84.6 and negative indicative value 99.5%. Test output was 99.1%. In bases of study results, ELISA sensitivity and specificity is lower than IFA method. Since use of ELISA method is more usual than IFA, severe control in production of kits is necessary to increase sensitivity and specificity,